Diffluent Internet Traffic and Characteristics Computation Based on Hadoop - Yong Liu; Jiangtao Luo; Shengxiong Deng; Xiaoping Wang (Dianxin kexue)
Internet traffic characteristics computation is an important step of internet traffic analysis, in the face of massive internet traffic data, parallel computing internet traffic characteristics is base to prompt the performance of internet traffic analysis. In order to solve the problems of poor expansibility and high cost that caused by the traditional stand-alone, an internet traffic characteristics analysis method based on MapReduce, which parallel processes diffluent internet traffic and characteristics computing, was proposed. By using the Hadoop platform, the actual data was analyzed and the common internet traffic characteristics were computed. Experiments show that the method is reliable to analyze the characteristic of the internet traffic and it is suitable for analyzing large traffic data.